Study of encapsulation and anticancer properties of plant extracts with probiotics - Holkem, Augusto Tasch (2020)
Probiotics and proanthocyanidin-rich cinnamon extract (PRCE) are sensitive to the processing and storage conditions in the foods in which they are added and to promote beneficial effects in individuals, especially in the prevention of colorectal cancer (CRC), they must resist passage through the gastrointestinal tract. Microencapsulation technologies have been used for decades to protecting bioactives materials. First, the objective of this work was to produce and evaluate the solid lipid microparticles covered by electrostatic interactions of polymers in which Lactobacillus paracasei (BGP1) (Lacticaseibacillus paracasei) and Bifidobacterium animalis subsp. lactis (BLC1) were either encapsulated alone or co-encapsulated with PRCE. In this case, microparticles with BLC1 and 5 g/100 g PRCE showed greater encapsulation efficiencies and greater retention of the bioactive materials stored at 7 °C for 120 days. Then, the second objective of this work was to evaluate the anticancer properties of free PRCE and in combination with BLC1 and their resistance under in vitro simulated gastrointestinal conditions. The co-encapsulation was advantageous because it protected these bioactives under gastrointestinal conditions, allowing their release into the intestine, where they could act in the early stages of CRC. So, the third aim of this work was to produce and evaluate a functional sugarcane juice enriched with BLC1 and PRCE, both in free and encapsulated forms. It was possible to produce sugarcane juice with non-encapsulated BLC1, but not with the addition of free PRCE, which in its free form reduced the viability of this microorganism to <1 log CFU/mL after 7 days. The microparticles were effective to protect BLC1 during juice storage and to maintain high contents of phenolic and proanthocyanidin compounds, although the products containing these had their viscosity altered and were less sensorially accepted than with free bioactives. The last aim of this work was to study the antiproliferative, antiradical and antioxidant activity, quinone reductase assay and apoptosis assay of extracts from blueberry and jabuticaba (free or in combination with probiotics). The extract that presented a greater chemopreventive effect compared to the others was the extract rich in water-soluble phenolic compounds from jabuticaba with BGP1 (JL), but there should be more studies to understand the interaction between them. It is concluded that the co-encapsulation of probiotics and PRCE was successful, providing these bioactives greater retention during storage, protection in simulated gastrointestinal conditions and incorporation in sugarcane juice. The combination of PRCE and BLC1 exhibited an anticancer property in the early stages of CRC, while JL demonstrated an action at different stages.